A. Álvarez-Ossorio Alvariño, J. Amelang, M. L. González Mezquita & S. Martínez Bermejo (coords.), 2023. Vidas fallidas. Aproximaciones al concepto de éxito y fracaso individual en la modernidad. Mar del Plata: EUDEM. 207 p. - Alejandro Sell Maestro (Anuario IEHS)
.